SnS2 Nanocrystalline-Anchored Three-Dimensional Graphene for Sodium Batteries with Improved Rate Performance - Li Zeng; Liping Zhang; Xingang Liu; Chuhong Zhang (Nanomaterials, 2020)
Tin disulfide (SnS2) is regarded as one of the most suitable candidates as the electrode material for sodium-ion batteries (SIBs). However, the easy restacking and volume expansion properties of SnS2 during the charge/discharge process lead to the destruction of the electrode structure and a decrease in capacity. We successfully synthesized a SnS2 nanocrystalline-anchored three-dimensional porous graphene composite (SnS2/3DG) by combining hydrothermal and high-temperature reduction methods. The SnS2 nanocrystalline was uniformly dispersed within the connected reduced graphene oxide matrix. The SnS2/3DG battery showed a high reversible capacity of 430 mAh/g after 50 cycles at 100 mA/g. The SnS2/3DG composite showed an excellent rate capability with the current density increasing from 100 mA/g to 2 A/g. The excellent performance of the novel SnS2/3DG composite is attributed to the porous structure, which not only promoted the infiltration of electrolytes and hindered volume expansion for the porous structure, but also improved the conductivity of the whole electrode, demonstrating that the SnS2/3DG composite is a prospective anode for the next generation of sodium-ion batteries.